Enhanced Antibacterial Efficacy of Ag(I), Cu(II), and Zn(II) Modified Sodalite Zeolite Against Escherichia coli and Staphylococcus aureus - Sriatun Sriatun; Khairini Pertiwi; Choiril Azmiyawati; Mukhammad Asy'ari; Damar Nurwahyu Bima; Nor Aida Zubir (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Sodalite zeolite modified with metal ions Ag+, Cu2+, Cu2+, and Zn2+ was successfully synthesized and evaluated for antibacterial activity. The research aims to obtain silver, copper, and zinc metal-modified sodalite separately and determine their antibacterial activity on Escherichia coli and Staphylococcus aureus bacteria. Sodalite zeolite was synthesized using ludox and sodium aluminate through hydrothermal methods, ensuring uniform crystal growth and optimal crystallinity, as confirmed by X-ray diffraction (XRD) analysis. The average particle sizes of the modified zeolites were determined to be 54.9 nm for Ag-Zeolite, 37.2 nm for Cu-Zeolite, and 28.56 nm for Zn-Zeolite, with structural changes observed through alterations in peak intensity. Scanning Electron Microscopy - Energy Dispersive X-ray (SEM-EDX) analysis showed no significant change in the zeolite’s morphology. In addition, the EDX results showed the presence of Ag (3.15%), Cu (3%), and Zn (2.41%) metals indicating successful ion exchange. Antibacterial assays revealed that Cu-Zeolite demonstrated superior efficacy inhibition zones against Escherichia coli (14.04±1.26) and Staphylococcus aureus (20.74±0.48), highlighting its potential as an antimicrobial agent. The mechanism of action involved the controlled release of metal ions, disrupting bacterial cell membranes and metabolic processes. Notably, Cu2+ ions exhibited the strongest antibacterial properties due to their smaller ionic radius and higher electronegativity than Ag+ and Zn2+. This research underscores the promising applications of metal-ion-modified sodalite zeolite in medical and environmental contexts.